A Clinico-pathological Correlation of Carcinoma Stomach and ABO Blood Group (Medicine Today, 2021)
Introduction: Stomach cancer related to higher rate for blood group A over other ABO types, a prospective assessment of relation between blood group and carcinoma stomach was performed with a view to state the role of ABO blood group in the development of gastric cancer with relationship of clinico-pathological variation. This study sought to investigate the relationship between ABO blood groups and the risk of gastric cancer as well as clinical pathological parameters.Materials and Methods: A Prospective random observational study carried between October 2005 to September 2006 in Dhaka Medical College Hospital, Department of Surgery & Radiotherapy. Maximum patients admitted in the surgery units with diagnosed case of carcinoma stomach were taken as sample or study population & rest attended in radiotherapy department in DMCH.Results: Among the 70 cases the mean age is 44.3(18-65) (M/F=4:1) years. All the information and data taken from Hospital records and patients themselves or first degree relatives. Results Blood group B-42.85%, A-34.28%, O- 15.71% only 11.42% gave positive family history. Histopathological report show's Adenocarcinoma 95% and among them blood group B 40% and A 31.42%. The differentiation of carcinoma stomach are categorized as Grade-I well differentiated, 37.14% cases moderately differentiated 15.71% and poorly differentiated 45.71%. Among them blood group B is more in case of poorly differentiated carcinoma 25.71%, blood group A is more in well differentiated carcinoma 17.14%.Conclusion: Blood group 'A' has an established relationship with carcinoma stomach. In this study it is found that blood group 'B' is more associated with carcinoma stomach and with poorly differentiated adenocarcinoma.Medicine Today 2021 Vol.33(1): 27-33